2020
DOI: 10.1097/psy.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Communication Skills Among Physicians: A Systematic Review of Existing Assessment Tools

Abstract: Objective The importance of physician training in communication skills for motivating patients to adopt a healthy life-style and optimize clinical outcomes is increasingly recognized. This study inventoried and systematically reviewed the psychometric properties of, and the skills assessed by, existing assessment tools used to evaluate communication skills among physicians. Methods This review was conducted in accordance with the PRISMA guidelines (PROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…In a national survey, most physicians (88%) acknowledged seeing better outcomes and higher caregiver satisfaction (73%) when they share information with families (American Association of Retired Persons, 2019). While physician communication training primarily consists of skills for information giving or gathering (Boucher et al, 2020), a recent systematic review of communication training programs for oncology providers found that there was no difference between trainees (physicians and nurses) who have had and have not had communication training (Moore et al, 2018). There continues to be a need to develop evidence-based communication skills training programs for physicians (Back et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a national survey, most physicians (88%) acknowledged seeing better outcomes and higher caregiver satisfaction (73%) when they share information with families (American Association of Retired Persons, 2019). While physician communication training primarily consists of skills for information giving or gathering (Boucher et al, 2020), a recent systematic review of communication training programs for oncology providers found that there was no difference between trainees (physicians and nurses) who have had and have not had communication training (Moore et al, 2018). There continues to be a need to develop evidence-based communication skills training programs for physicians (Back et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature on existing tools for assessing physicians' communication skills, which looked at 45 instruments in 57 studies, found an extensive heterogeneity between the tools used, highlighting the lack of consensus [7]. This analysis concluded that it is necessary to develop unitary training methods for health professionals and to use assessment tools that are easy to manage, simple, time-sparing, standardized, validated, easy to reproduce, and generally accepted by users.…”
Section: Patientsmentioning
confidence: 99%
“…Healthcare professionals' attitudes are also affected when there is a divergence between them and patients or their relatives. The negative impact of con icts can be diminished or even avoided if the patient is well informed, is involved in making choices about his health, and can explain why he disagrees with the doctor [7]. Besides, the increase in patient satisfaction is associated with a decrease in rates of malpractice complaints or claims [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature on the quality of existing communication assessment tools among HCPs revealed a great deal of heterogeneity over the 45 different assessment tools that were identified. This review also indicated that few tools were developed using appropriate theoretical models (49%), and many failed to clearly define or describe the communication competencies they were designed to evaluate (19%) [ 17 ]. In addition, 65% used scoring methods that required extensive training on the part of external assessors, and 93% of the tools required the use of standardized (ie, a person playing the role of a patient; 61%) or real patients (32%) to complete their evaluations [ 17 ], potentially undermining the feasibility of implementing this type of evaluation in real life .…”
Section: Introductionmentioning
confidence: 99%
“…This review also indicated that few tools were developed using appropriate theoretical models (49%), and many failed to clearly define or describe the communication competencies they were designed to evaluate (19%) [ 17 ]. In addition, 65% used scoring methods that required extensive training on the part of external assessors, and 93% of the tools required the use of standardized (ie, a person playing the role of a patient; 61%) or real patients (32%) to complete their evaluations [ 17 ], potentially undermining the feasibility of implementing this type of evaluation in real life . Existing competency assessment tools are hence complex, invasive, time-consuming, and impractical for use in many medical contexts.…”
Section: Introductionmentioning
confidence: 99%